2020
DOI: 10.1097/md.0000000000023314
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of multi-omics data identifying molecular biomarker candidates and epigenetically regulatory targets associated with retinoblastoma

Abstract: Retinoblastoma (RB) is the commonest malignant tumor of the infant retina. Besides genetic changes, epigenetic events are also considered to implicate the occurrence of RB. This study aimed to identify significantly altered protein-coding genes, DNA methylation, microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and their molecular functions and pathways associated with RB, and investigate the epigenetically regulatory mechanism of DNA methylation modification and non-coding RNAs on key genes of RB via bioinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Future studies may expand upon these results by considering more downstream analytes, such as DNA methylation or RNA expression, to assess biological differences between patients either dependent or independent of DNA mutations. For example, recent studies have considered genome-wide methylation and found expression patterns unique to retinoblastoma, suggesting their importance to oncogenesis [ 40 , 41 ]. Further clinical assessment of patient phenotypes alongside various biological measurements may yield important insight into the progression of retinoblastoma from DNA mutation to unique clinicopathological features of retinoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may expand upon these results by considering more downstream analytes, such as DNA methylation or RNA expression, to assess biological differences between patients either dependent or independent of DNA mutations. For example, recent studies have considered genome-wide methylation and found expression patterns unique to retinoblastoma, suggesting their importance to oncogenesis [ 40 , 41 ]. Further clinical assessment of patient phenotypes alongside various biological measurements may yield important insight into the progression of retinoblastoma from DNA mutation to unique clinicopathological features of retinoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…As the catalytic subunit of RR, RRM2 is the rate-limiting enzyme for DNA synthesis and repair, and its expression level is associated with the sensitivity of cancer cells to chemotherapy drugs and endocrine therapy drugs [ 10 , 25 , 28 ]. Previous studies indicated that in neuroblastoma, a highly malignant brain tumor, patients with high RRM2 expression are associated with a worse prognosis [ 29 ]. A previous study also suggests that RRM2 upregulation contributes to RB cell cycle progression [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the study of Zeng et al demonstrated that bioinformatics analysis of the GSE97508 dataset, with the approach of examining epigenetic factors in retinoblastoma, can create significant diagnostic or therapeutic methods. TTK , RRM2 , and CDK1 were selected as candidates [ 55 ]. In the present study, RRM2 was also selected as a candidate gene related to miR-204.…”
Section: Discussionmentioning
confidence: 99%